The Prognostic Value of Sarcopenia and Myosteatosis in Biliary Tract Cancer After Palliative Treatment With Radiation-Emitting Metallic Stent - Chen, Qi; Lu, Jian; Lu, Xun; Yao, Xi-Juan; Zhang, Xuan-Pu; Wang, Shang-Yuan; Guo, Jin-He (Frontiers in Surgery, 2022)
Background: Radiation-emitting metallic stent (REMS) placement is increasingly used for malignant biliary obstruction (MBO) caused by unresectable biliary tract carcinoma (UBTC) in clinical practice. The study is aimed to evaluate the prognostic value of sarcopenia, myosteatosis, and their combination on overall survival (OS) in patients treated with REMS for UBTC. Methods Patients diagnosed with UBTC who underwent REMS placement between January 2013 and May 2021 were included consecutively in this retrospective study. Sarcopenia and myosteatosis were defined based on skeletal muscle index (SMI) and skeletal muscle attenuation (SMA), respectively, which were measured by computer tomography (CT) images on the level of the third lumbar vertebral body before REMS placement. Patients were categorized into two groups by sex-specific cutoff value for sarcopenia and myosteatosis, and OS rates were compared between the groups. Univariate and multivariate cox regression analyses were used to assess factors associated with OS. Results Data of 135 patients included were retrospectively reviewed and analyzed. Median OS was 7.17 months in total cohort. Patients in the sarcopenia group had significant poorer OS than those in the non-sarcopenia group (median: 3.23 vs. 11.60 months, p < 0.001). OS was shorter in patients with myosteatosis than those without myosteatosis (median: 4.40 vs. 9.17 months, p < 0.001). Sarcopenia (odds ratio [OR] = 9.61; 95% CI = 5.41–17.09; p < 0.001) and myosteatosis (OR = 1.70; 95% CI = 1.13–2.57; p = 0.012) were significantly associated with OS. Combining sarcopenia and myosteatosis (CSM) showed a better predictive accuracy in OS than either one (area under curves: CSM vs. sarcopenia = 0.760 vs. 0.698, p = 0.049; CSM vs. myosteatosis = 0.760 vs. 0.671, p = 0.006). Conclusion Sarcopenia and myosteatosis are negative predictors of survival in patients who underwent REMS placement for UBTC. CSM seemed to show a better prognostic value than either sarcopenia or myosteatosis alone. They can be used preoperatively for risk evaluation.